The Application of Artificial Bee Colony Algorithm to Optimizing Vehicle Routes Problem - Yenny Anggreini Sarumaha; Dede Ridho Firdaus; Irwan Moridu (Yayasan Gema Bina Nusantara, 2023)
The problem of vehicle routing with capacity is a combinatorial optimization problem that is included in the NP-Hard category. In this article, we suggest an artificial bee colony algorithm, which is a technique inspired by the clever behavior of bees in searching for food sources. To achieve the best outcomes, the artificial bee colony algorithm will be developed in conjunction with other algorithms. To determine how well the artificial bee colony method handles the issue of optimizing vehicle routes with capacity, eight distinct benchmark problems will be completed and then contrasted with other algorithms. The output of this research is a matrix showing the sequence of vehicle routes formed.